Ocean surface current multiscale observation mission (OSCOM): Simultaneous measurement of ocean surface current, vector wind, and temperature. (April 2021) - Du, Yan; Dong, Xiaolong; Jiang, Xingwei; Zhang, Yuhong; Zhu, Di; Sun, Qiwei; Wang, Zhenzhan; Niu, Xinhua; Chen, Wen; Zhu, Cheng; Jing, Zhiyou; Tang, Shilin; et al.
Highlights: A satellite concept Ocean Surface Current multiscale Observation Mission is proposed. OSCOM will directly measure surface currents with a resolution of ~10 km. OSCOM will observe ocean surface current, vector wind, and temperature simultaneously. OSCOM will help the study on non-equilibrium ocean state and air-sea interaction. OSCOM will provide an improved pathway to data assimilation for ocean prediction. Abstract: Ocean current is one of the major drivers of water mass, energy, and biogeochemical cycles in the global ocean–atmosphere boundary layer and also a key variable in the formation of extreme climate events (e.g., El Niño). Direct measurement of the global ocean surface current is of great scientific interest and application value for understanding multiscale ocean dynamics, air-sea interaction, ocean mass and energy balance, and ocean carbon budget, as well as their variabilities under climate change. This paper reviews the state-of-the-art developments of ocean dynamics and technology on the observation of multiscale ocean circulation and related scientific frontiers. Presently, measurements of global ocean surface currents, which are mainly geostrophically derived from satellite altimeter data, are only available to resolve quasi-geostrophic current at large- to meso-scale in the off-equatorial open ocean. This becomes a bottleneck impeding the application and the development of ocean circulation dynamics. With the ambition of breaking the bottleneck, Ocean Surface Current multiscale Observation Mission (OSCOM) will launch a satellite equipped with a Doppler Scatterometer to directly measure ocean surface currents for the first time with a very high horizontal resolution of 5–10 km and a 3-day global coverage. Through carrying a Surface Temperature Infrared Radiometer and a Surface Temperature Microwave Radiometer, the OSCOM satellite is supposed to have the capability of observing ocean surface current, ocean surface vector wind, and sea surface temperature simultaneously. With a cutting-edge design, OSCOM will provide an in-depth picture of non-equilibrium ocean state and air-sea interaction from mesoscale to submesoscale, and helps to construct the fine structure of deep ocean current through a combination with Array for Real-time Geostrophic Oceanography profiling. Those direct measurements and derived dynamic parameters will further facilitate analyses of ocean carbon budget and ocean biogeochemical cycle, and provide a novel and improved pathway to data assimilation, coupling of General Circulation Models, and the Earth System Modelling for ocean prediction and climate change.